Intrathecal methotrexate prophylaxis and central nervous system relapse in patients with diffuse large B-cell lymphoma following rituximab plus cyclophosphamide, doxorubicin, vincristine and prednisone. Issue 3 (March 2015) - Tomita, Naoto; Takasaki, Hirotaka; Ishiyama, Yasufumi; Kishimoto, Kumiko; Ishibashi, Daisuke; Koyama, Satoshi; Ishii, Yoshimi; Takahashi, Hiroyuki; Numata, Ayumi; Watanabe, Reina; Tachibana, Takayoshi; Ohshima, Rika; et al.
Abstract: This study evaluated the efficacy of central nervous system (CNS) prophylaxis using intrathecal methotrexate (IT-MTX) in patients with diffuse large B-cell lymphoma (DLBCL). We retrospectively studied 322 patients who achieved first complete remission (CR) after rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) therapy. The CNS prophylaxis consisted of four doses of IT-MTX (15 mg) with hydrocortisone (25 mg) administered after CR was achieved. Forty patients (12%) received CNS prophylaxis (group A) and 282 patients (88%) did not (group B). Three patients in group A (8%) and eight in group B (3%) experienced isolated CNS relapse during the first CR, although this difference was not statistically significant ( p = 0.14). Ten of 11 CNS relapses occurred in the brain parenchyma with ( n = 3) or without ( n = 7) leptomeningeal involvement, and the remaining patient had exclusive leptomeningeal involvement. In patients with DLBCL attaining CR after R-CHOP, IT-MTX administration was insufficient to prevent CNS relapse.